2017
DOI: 10.1186/s12906-017-1586-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of anti-cancer effects and mechanisms of Zuo-Jin-Wan and its alkaloid components in vitro and in orthotopic HepG2 xenograft immunocompetent mice

Abstract: BackgroundZuo-Jin-Wan (ZJW), a two-herb formula consisting of Coptis chinensis (CC) and Evodia rutaecarpa (ER), is commonly used in traditional Chinese medicine for the treatment of cancers. However, the efficacies and mechanisms of ZJW and its alkaloid components on cancers are still unclear.MethodsHere we investigated the anti-cancer effects and mechanisms of ZJW, CC, ER, berberine, and evodiamine in cells and in intrahepatic xenograft mice.ResultsTreatment of HepG2 cells with ZJW, CC, ER, berberine, and evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
(48 reference statements)
0
37
0
Order By: Relevance
“…Zuo Jin Wan (ZJW) is a well-known drug pair composed of C. chinensis Franch and Fructus rutaecarpa Benth (Wuzhuyu), which was prescribed to remove heat and dampness from liver. Recent works have identified antineoplastic activity of ZJW in several types of tumors including gastric cancer (Tang et al, 2012), colorectal cancer (Sui et al, 2013), breast cancer (Du et al, 2013), and liver cancer (Chao et al, 2011;Chou et al, 2017). The mode of action underlying the antiproliferation effect of ZJW on these malignancies involved the induction of mitochondria-dependent apoptosis (Xu et al, 2014).…”
Section: Ancient Herbal Formulas In Liver Cancer Treatmentmentioning
confidence: 99%
“…Zuo Jin Wan (ZJW) is a well-known drug pair composed of C. chinensis Franch and Fructus rutaecarpa Benth (Wuzhuyu), which was prescribed to remove heat and dampness from liver. Recent works have identified antineoplastic activity of ZJW in several types of tumors including gastric cancer (Tang et al, 2012), colorectal cancer (Sui et al, 2013), breast cancer (Du et al, 2013), and liver cancer (Chao et al, 2011;Chou et al, 2017). The mode of action underlying the antiproliferation effect of ZJW on these malignancies involved the induction of mitochondria-dependent apoptosis (Xu et al, 2014).…”
Section: Ancient Herbal Formulas In Liver Cancer Treatmentmentioning
confidence: 99%
“…The insoluble materials were removed by centrifugation at 3,000 rpm for 30 min and stored at 4 • C. Extracts were dissolved in water at a concentration of 100 mg/ml and stored at −20 • C until use. The method of preparation of CHM extract was described previously (9,13). The HPLC profile of BHSSC is shown in Figure S1.…”
Section: Preparation Of Chinese Herbal Medicine Extractmentioning
confidence: 99%
“…Chinese herbal medicine (CHM) has a long history in the treatment of various human diseases, including tumors, infections, and autoimmune diseases, in Asian countries. Some studies have demonstrated that CHM may enhance antitumor activity through increasing tumor apoptosis (7)(8)(9), inhibiting angiogenesis (10), and modulating the tumor microenvironment (11). In a large-scale clinical analysis, patients with malignant tumors who sought adjunctive CHM treatment had a better overall survival rate than patients who did not undergo CHM treatment (9,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations